Re-excavating Jerusalem : archival archaeology - Prag, Kay (The Schweich lectures of the British Academy, 2019)
The excavations of Jerusalem by Dame Kathleen Kenyon in the 1960s excited great interest, and the on-going study and publication continues to provide new insights and re-interpretations. This well-illustrated overview of the archive reconsiders many aspects of Jerusalem's long history, from the Bronze Age to the 15th century AD